Penerapan Instrumen pada Anak Berkebutuhan Khusus Kategori Disgrafia di SKH Nurbayan 1 (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Inclusive education is an educational service system that provides opportunities for all students, including children with special needs, to learn together in a shared educational environment. One such child with special needs who requires special attention in the learning process is a child with writing difficulties (dysgraphia). This study aims to describe the application of assessment instruments, as well as the writing abilities and challenges experienced by students with dysgraphia at SDN Nurbayan 1, Tangerang City. The research method used was descriptive qualitative research, with data collection techniques including observation, interviews, and documentation. The study subjects consisted of a student with dysgraphia and the classroom teacher. The results showed that the student experienced challenges in fine motor skills, letter and word formation, writing consistency, and writing speed. The application of assessment instruments, such as observation sheets, anecdotal notes, and interviews, provided a comprehensive picture of the student's abilities and learning needs. Although technical writing skills were still relatively low, the student demonstrated a strong interest and motivation in writing activities. Therefore, the application of appropriate, flexible, and process-oriented assessment instruments is essential to support the development of the writing abilities of children with dysgraphia in an inclusive educational environment.